2020
DOI: 10.4236/fns.2020.116038
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Optimal Maternal and Child Feeding Practices in Pastoralist Areas of Somali Region, Eastern Ethiopia: A Qualitative Study

Abstract: Maternal and child nutrition is critical for child health and survival. Appropriate feeding practices are of fundamental importance for health, nutrition, survival and development of infants and children. In pastoral areas of Ethiopia, barriers related to culture, knowledge, social norms, beliefs, behaviors, decision making in the household and burden of other responsibilities contribute to nutritional status of women and children to deteriorate. Policies and strategies are recommending assessment of barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…The main reasons to give pre-lacteal feedings to children were a cultural perspective and the expectation of insufficient breast milk. These findings corroborated the findings of previous studies ( 18 , 26 – 30 ). The causes of milk being the commonest pre-lacteal feeding in the Afar region can be attributed to the pastoralist nature of the Afar people, whose income depends on animal products.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main reasons to give pre-lacteal feedings to children were a cultural perspective and the expectation of insufficient breast milk. These findings corroborated the findings of previous studies ( 18 , 26 – 30 ). The causes of milk being the commonest pre-lacteal feeding in the Afar region can be attributed to the pastoralist nature of the Afar people, whose income depends on animal products.…”
Section: Discussionsupporting
confidence: 93%
“…Animal products are highly consumed in pastoral areas where cow or goat milk is a major part of the diet for pastoralist children in addition to breastfeeding (17). The main reasons for practicing pre-lacteal feeding are the assumption of cultural taboos and beliefs (26)(27)(28), and insufficient breast milk production (18,29,30). Mothers with a lower socioeconomic status commonly practice pre-lacteal feeding (31).…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts to improve breastfeeding practices in sub-Saharan Africa,48 the belief that breast milk is insufficient to hydrate babies and that water is needed to quench their thirst still prevails in several societies 12 49–51. In the commune of Bobo-Dioulasso, provision of supplementary fluids (particularly water) was widespread.…”
Section: Discussionmentioning
confidence: 99%
“…This situation could be explained by socio-cultural constraints. Indeed, some authors had reported that in Sudan and Ethiopia, the non-consumption of some food groups such as eggs was linked to socio-cultural considerations [34,35]. Particularly for non-breastfed children, dairy products were heavily consumed.…”
Section: Discussionmentioning
confidence: 99%